MBRS-26. CDK7 MEDIATED TRANSCRIPTIONAL PROCESSIVITY OF DNA REPAIR NETWORKS REGULATES SENSITIVITY TO RADIATION IN MYC DRIVEN MEDULLOBLASTOMA - Veo, Bethany (Neuro Oncol, 2020)
Myc-driven Medulloblastoma remains a major therapeutic challenge due to frequent metastasis and a poor 5-year survival rate. Myc overexpression results in transcriptional dysregulation, proliferation, and survival of malignant cells. To identify therapeutic targets in Myc-amplified medulloblastoma we performed a CRISPR-Cas9 essentiality screen targeting 1140 genes annotated as the druggable genome. The cyclin-dependent kinase, CDK7, was identified as a top candidate. CDK7 phosphorylates the c-terminal domain of RNA Pol II facilitating transcriptional initiation and elongation. We subjected Myc-amplified cells treated with CDK7 inhibitors to whole transcriptomic analysis. The resultant data revealed gene networks mediating DNA repair were functionally repressed. Consistent with this data, ChIP-sequencing showed the most significant reduction in RNA Pol II and Myc promoter occupancy within a subset of DNA repair genes including BRCA2 and RAD51 but not across the whole genome. These data suggest that inhibition of CDK7 mechanistically limits Myc driven transcriptional processivity of DNA repair networks. Further, evaluation of genes mediating DNA repair show a muted response to DNA damage and increased cell death with CDK7 inhibition. We next evaluated Myc-amplified MB cell response to ionizing radiation in vitro and in vivo with CDK7 inhibition. Inhibition of CDK7 enhanced radiation sensitivity of Myc MB cells by potentiating DNA damage. Further, cotreatment produced decreased MRI T2 tumor volumes and enhanced survival benefit in orthotopic PDX xenografted mice compared to radiation alone. Our studies establish a mechanism for selective inhibition of Myc-driven MB by CDK7 inhibition combined with radiation as a viable therapeutic strategy for Myc-amplified medulloblastoma.